Adoção de práticas de BYOD à luz dos princípios da teoria effectuation - Silva, Marcos Paulo da (2016)
The following study seeks to comprehend in which way Information Technology (IT) users and manager conduct the adoption of Bring Your Own Device (BYOD) practices, under the light of Effectuation theory principles. The theoretical framework brings discussions on the context of consumerization, its applications and implications for organizations and individuals, the Effectuation theory approach, the effectual logic, its principles and process. This is an exploratory-descriptive study, which uses both qualitative and quantitative research methods by means of one single case study, in which took part 42 users and the IT manager of a company that has been operating for the last 49 years in the retailer/wholesaler sector in the city of Natal/RN. Descriptive statistics, logistic regression (bootstrap), Pearson correlation and Mann-Whitney U test were used for the analysis of the data collected from the IT users, along with the aid of the Statistical Package for the Social Sciences (SPSS) software, version 21. Categorical content analysis – thematic analysis – was used for the analysis of the interview granted by the IT manager, with the support of the ATLAS.ti software, version 7.5.1.5. The research evinces, by means of metainferences, the existence of divergences between the adoption of BYOD practices by IT users – effectual profile prevalent – and by the company, represented by the IT manager – causal profile. The management aspects concerning unforeseen events mitigation, information safety and control enforcing the used towards work activities go against IT users’ perspective, which assume that, by means of BYOD practices, it is possible to attain an autonomous and innovation-biased performance, due to contingencies exploration and the establishment of partnerships with coworkers and/or clients and/or suppliers. Nevertheless, both IT users and manager converge regarding the perspective towards the benefits to the organization activities, in terms of employees’ satisfaction, to the improvement of customer’s services and to the realization of partnerships for the adoption, since the IT manager perceives the availability of IT infrastructure by the company so that the employees may use their own devices as a partnership. It is concluded that the establishment of partnerships encompass the occurrence of interactions between the used and the IT manager, which enhance the human action upon the construction of BYOD practices adoption, especially when intelligent altruism is present. It must be highlighted that, in the adoption policy, the user educational level and the perspective that these practices adoption occur due to the possibility of the devices being used anywhere must be considered, according to the logit models, in order to optimize the meeting of the demands from most IT users of the company.